Mycobacterium kansasii Subtype I Is Associated With Clarithromycin Resistance in China - Li, Yanming; Pang, Yu; Tong, Xunliang; Zheng, Huiwen; Zhao, Yanlin; Wang, Chen (Frontiers in Microbiology, 2016)
Mycobacterium kansasii is the second most common cause of slowly growing nontuberculous mycobacteria (NTM) diseases in China. The aim of the present study was to analyze M. kansasii subtypes isolated from patients in China, and to explore the antimicrobial susceptibility of the differentiation among these diverse subtypes. A total of 78 M. kansasii strains from 16 provinces of China were enrolled in this study. Amikacin (AMK) was the most highly active against M. kansasii strains, and only 4 isolates (5.1%) exhibited in vitro resistance to AMK. The percentage of levofloxacin (LFX) resistant strains among the 78 M. kansasii isolates was 39.7% (31/78), which was significantly higher than that of moxifloxacin (MOX) (16.7%, P=0.001) and gatifloxacin (GAT) (19.2%, P=0.005). By using PCR-restriction fragment analysis of the hsp65 gene (PRA), all the isolates were classified as four different subtypes. Of these four subtypes, M. kansasii subtype I was the most frequent genotype in China, accounting for 71.8% (56/78) of M. kansasii isolates. Resistance to clarithromycin (CLA) was noted in 26.8% (15/56) of subtype I isolates, which was significant higher than that of other subtypes (4.5%, P=0.031). DNA sequencing revealed that the presence of mutations in 23S rRNA was associated with 56.2% (9/16) of CLA-resistant M. kansasii isolates. In conclusion, our data demonstrate that AMK is the most active agent against M. kansasii in vitro, while the high proportion of CLA resistance is noted in M. kansasii isolates. In addition, the predominant subtype I is associated with CLA resistance in China.